Glass substrate for Micro LED and Micro LED
By adjusting the proportion of oxides in the glass substrate, the problem of traditional Micro LED glass substrates being unable to balance high glass transition temperature and low melting temperature was solved, achieving a cost-effectiveness balance and improving the performance of the glass substrate.
Patent Information
- Application Number
- CN202411512861.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional glass substrates for Micro LEDs are difficult to simultaneously possess both high glass transition temperatures and low melting temperatures, resulting in high production costs and making it difficult to meet the cost requirements of Micro LED products.
Glass substrates composed of oxides in specific proportions, including SiO2, Al2O3, Li2O, Na2O, K2O, MgO, CaO, BaO, SrO, B2O3, P2O5, and ZrO2, achieve a balance between high glass transition temperature and low melting temperature by adjusting the composition ratio, thereby reducing production costs and improving glass performance.
This approach achieves a balance between high glass transition temperature and low melting temperature for Micro LED glass substrates, reducing production costs. Furthermore, the addition of ZrO2 reduces furnace refractory erosion and improves the strength and chemical stability of the glass.
Smart Images

Figure SMS_5 
Figure SMS_6 
Figure SMS_7
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and in particular to a glass substrate for Micro LED and Micro LED. Background Art
[0002] COG (Chip on Glass) refers to the technology of bonding LED chips directly to glass substrates and using TFT (Thin Film Transistor) to achieve display. Common LED screens bond LED chips to PCB printed circuit boards, while COG technology replaces PCBs with glass substrates. Glass-based Micro LED is a new display technology that uses micron-sized LEDs as light-emitting elements and integrates them onto glass substrates. The production of glass-based Micro LEDs requires the selection of high-quality glass substrates to improve the adhesion and luminous efficiency of LEDs.
[0003] It is difficult for traditional Micro LED glass substrates to have both a high glass transition temperature and a low melting temperature. Summary of the invention
[0004] Based on this, it is necessary to provide a glass substrate for Micro LED and Micro LED. The glass substrate for Micro LED of the present application can have a higher glass transition temperature and a lower melting temperature at the same time.
[0005] In a first aspect, the present application provides a glass substrate for Micro LED, which, as a basic composition, is expressed in terms of mass percentage based on oxides and includes the following components:
[0006] 53%~65% SiO2, 5%~17% Al2O3, 0~3% Li2O, 1%~10% Na2O, 0~2% K2O, 0.1%~10% MgO, 9%~16% CaO, 0~2% BaO, 0~3% SrO, 2%~6% B2O3, 0~3% P2O5 and 0.01%~1% ZrO2.
[0007] In some of the embodiments, the sum of the mass percentages of SiO2 and Al2O3 is 66% to 75%.
[0008] In some embodiments, the sum of the mass percentages of Li2O, Na2O and K2O is 4% to 10%.
[0009] In some embodiments, the sum of the mass percentages of MgO, CaO, BaO and SrO is 14% to 23%.
[0010] In some embodiments, the melting temperature of the glass substrate for Micro LED is T2, 1400°C<T2<1500°C.
[0011] In some embodiments, the glass transition temperature of the glass substrate for Micro LED is T g , 660℃<T g <720℃.
[0012] In some embodiments, the clarification temperature of the Micro LED glass substrate is T3, 1200°C<T3<1300°C.
[0013] In some embodiments, the difference between the clearing temperature and the upper limit of crystallization of the glass substrate for Micro LED is ΔT, and 100°C≤ΔT≤176°C.
[0014] In some embodiments, the sum of the mass percentages of Na2O and K2O is a, the sum of the mass percentages of Li2O, Na2O and K2O is b, the sum of the mass percentages of SiO2 and Al2O3 is c, and 0.14≤ :E≤0.5.
[0015] In some of the embodiments, the mass percentage of SiO2 is 56% to 63%.
[0016] In some of the embodiments, the mass percentage of Al2O3 is 8% to 16%.
[0017] In some embodiments, the mass percentage of Li2O is 0%-1%.
[0018] In some of the embodiments, the mass percentage of Na2O is 1% to 6%.
[0019] In some embodiments, the mass percentage of K2O is 0%-1%.
[0020] In some embodiments, the mass percentage of MgO is 1% to 9%.
[0021] In some embodiments, the mass percentage of CaO is 10% to 16%.
[0022] In some of the embodiments, the mass percentage of P2O5 is 0-2.5%.
[0023] In a second aspect, the present application provides a Micro LED, comprising any one of the above-mentioned glass substrates for Micro LED.
[0024] The above-mentioned glass substrate for Micro LED can have both a higher glass transition temperature and a lower melting temperature. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0028] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0029] An embodiment of the present application provides a glass substrate for Micro LED, which, as a basic composition, expressed in mass percentage based on oxides, includes the following components: 53%~65% SiO2, 5%~17% Al2O3, 0~3% Li2O, 1%~10% Na2O, 0~2% K2O, 0.1%~10% MgO, 9%~16% CaO, 0~2% BaO, 0~3% SrO, 2%~6% B2O3, 0~3% P2O5 and 0.01%~1% ZrO2.
[0030] The above-mentioned glass substrate for Micro LED can have both a higher glass transition temperature and a lower melting temperature.
[0031] Furthermore, the most commonly used glass substrate for Micro LED is still TFT (thin film transistor) glass substrate, which is high in cost and over-performance, and does not meet the cost requirements of Micro-LED products. The glass substrate in this application uses mineral raw materials while meeting product requirements, and can reduce the melting temperature of glass, thereby reducing the production cost of the glass substrate.
[0032] Furthermore, the glass substrate for Micro LED of the present application can achieve a difference between the clarification temperature and the upper limit of crystallization greater than or equal to 100°C while achieving a higher melting temperature, so that the glass substrate for Micro LED of the present application can be produced by float forming.
[0033] Furthermore, during the production process, magnesium in the glass liquid has a strong corrosive effect on kiln refractory materials, especially high zirconium bricks. A small amount of zirconium is added to the raw materials of the glass substrate of the present application, so that the glass liquid can reduce the erosion of kiln refractory materials during the production process. At the same time, zirconium can also act as a network former, increase the glass transition temperature of the glass and reduce the thermal expansion coefficient of the glass to meet the performance requirements of the product. Expressed as a percentage by mass of an oxide basis, the mass percentage of ZrO2 is 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.82%, 0.84%, 0.86%, 0.88%, 0.9%, 0.92%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99% or 1%. Alternatively, the mass percentage of ZrO2 may also be within the range between any two of the mass percentages mentioned above.
[0034] Silicon dioxide (SiO2) is the main component of the glass skeleton. SiO2 can improve the strength and chemical stability of glass, as well as the scratch resistance of glass, and can make glass obtain a lower thermal expansion coefficient. The mass percentage of SiO2 is 53%~65% expressed as the mass percentage of oxide basis. If the mass percentage of SiO2 is too small, the network structure of the main body of the glass will be poorly formed, resulting in poor mechanical properties of the glass. If the mass percentage of SiO2 is too large, the proportion of silicon-oxygen skeleton structure in the glass will be too high, resulting in the melting temperature of the glass being too high during the production process, thereby increasing the energy consumption of production, and easily causing defects such as bubbles and stones during the production process. Optionally, the mass percentage of SiO2 is 53%, 53.5%, 54%, 54.5%, 55%, 55.5%, 56%, 56.5%, 57%, 57.5%, 58%, 58.5%, 59%, 59.5%, 60%, 60.5%, 61%, 61.5%, 62%, 62.5%, 63%, 63.5%, 64%, 64.5% or 65%. Alternatively, the mass percentage of SiO2 can also be within the range between any two of the above mass percentages. Preferably, the mass percentage of SiO2 is 56% to 63%.
[0035] Alumina (Al2O3) can increase the glass transition temperature of glass and enhance its chemical stability and elastic modulus. The mass percentage of Al2O3 is 5% to 17% expressed as a mass percentage of oxide basis. If the mass percentage of Al2O3 is too small, the glass transition temperature of the glass is too low. If the mass percentage of Al2O3 is too large, the glass raw material will become extremely difficult to melt, resulting in a reduced melting effect of the glass raw material, making it difficult to meet production requirements. Optionally, the mass percentage of Al2O3 is 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5% or 17%. Alternatively, the mass percentage of Al2O3 can also be within the range between any two of the above mass percentages. Preferably, the mass percentage of Al2O3 is 8% to 16%.
[0036] Lithium oxide (Li2O) can be used as a flux to reduce the melting point of glass, but the effect of Li2O on the thermal expansion coefficient of glass is smaller than that of Na2O and K2O. The mass percentage of Li2O is 0% to 3% expressed as a mass percentage of an oxide basis. Optionally, the mass percentage of Li2O is 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%. Alternatively, the mass percentage of Li2O can also be within the range between any two of the above mass percentages. Due to the high price of lithium carbonate raw materials, the amount of Li2O used in the glass raw materials in actual production is usually small. Preferably, the mass percentage of Li2O is 0%~1%.
[0037] Sodium oxide (Na2O) as a flux can improve the melting properties of glass and enable the glass to obtain a lower melting temperature. Expressed as a mass percentage of oxide basis, the mass percentage of Na2O is 1% to 10%. When the mass percentage of Na2O is too large, the network structure of the glass will deteriorate, resulting in reduced stability of the mechanical and thermal properties of the glass and increased thermal expansion coefficient. Optionally, the mass percentage of Na2O is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%. Alternatively, the mass percentage of Na2O can also be within the range between any two of the above mass percentages. Preferably, the mass percentage of Na2O is 1% to 6%.
[0038] Potassium oxide (K2O) as a flux can improve the melting properties of glass and enable the glass to obtain a lower melting temperature. Expressed as a mass percentage based on oxide, the mass percentage of K2O is 0-2%. Optionally, the mass percentage of K2O is 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%. Alternatively, the mass percentage of K2O can also be within the range between any two of the above mass percentages. Preferably, the mass percentage of K2O is 0%-1%.
[0039] Magnesium oxide (MgO), calcium oxide (CaO), strontium oxide (SrO) and barium oxide (BaO) can reduce the viscosity of glass at high temperatures and promote the melting and clarification of glass. At low temperatures, they can enhance the stability of the glass network space and have a good repairing effect on the voids in the silicon-aluminum-oxygen network structure of the glass. To a certain extent, they can reduce the thermal expansion coefficient of the glass. At the same time, they can also increase the low-temperature viscosity of the glass and increase the glass transition temperature of the glass.
[0040] Expressed as a mass percentage of an oxide basis, the mass percentage of MgO is 0.1% to 10%. Optionally, the mass percentage of MgO is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.2%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9% or 10%. Alternatively, the mass percentage of MgO may also be within the range between any two of the above mass percentages. Preferably, the mass percentage of MgO is 1% to 9%.
[0041] Expressed as a mass percentage of oxide basis, the mass percentage of CaO is 9% to 16%. Optionally, the mass percentage of CaO is 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5% or 16%. Alternatively, the mass percentage of CaO may also be within the range between any two of the above mass percentages. Preferably, the mass percentage of CaO is 10% to 16%.
[0042] The mass percentage of SrO is 0-3% expressed as a mass percentage of oxide. Alternatively, the mass percentage of SrO is 0, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%. Alternatively, the mass percentage of SrO may also be within the range between any two of the above mass percentages.
[0043] The mass percentage of BaO is 0-2% expressed as a mass percentage of oxide. Alternatively, the mass percentage of BaO is 0, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%. Alternatively, the mass percentage of BaO may be within the range between any two of the above mass percentages.
[0044] Boron oxide (B2O3) can significantly reduce the thermal expansion coefficient of glass and increase the glass transition temperature of glass. The mass percentage of B2O3 is 2% to 6% expressed as a mass percentage of oxide basis. B2O3 first acts as a network former when added to glass, which will increase the viscosity of the glass. Gradually increasing the amount of B2O3 added will reduce the high-temperature viscosity of the glass. When the mass percentage of B2O3 is too low, the thermal expansion coefficient of the glass is high and the viscosity is high. When the mass percentage of B2O3 is too high, it is easy to cause stratification of the glass liquid, which does not meet production requirements. Optionally, the mass percentage of B2O3 is 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.2%, 5.4%, 5.6%, 5.8% or 6%. Alternatively, the mass percentage of B2O3 can also be within the range between any two of the above mass percentages.
[0045] Phosphorus pentoxide (P2O5) can further increase the glass transition temperature of the glass. Expressed as a mass percentage based on oxide, the mass percentage of P2O5 is 0-3%. When the mass percentage of P2O5 is too high, the thermal expansion coefficient of the glass will increase significantly, and the viscosity of the glass will increase, resulting in a decrease in the surface compressive stress value. Optionally, the mass percentage of P2O5 is 0, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%. Alternatively, the mass percentage of P2O5 can also be within the range between any two of the above mass percentages. Preferably, the mass percentage of P2O5 is 0-2.5%.
[0046] In some embodiments, the sum of the mass percentages of SiO2 and Al2O3 is 66% to 75%. Optionally, the sum of the mass percentages of SiO2 and Al2O3 is 66%, 66.5%, 67%, 67.5%, 68%, 68.5%, 69%, 69.5%, 70%, 70.5%, 71%, 71.5%, 72%, 72.5%, 73%, 7.5%, 74%, 74.5% or 75%. Alternatively, the sum of the mass percentages of SiO2 and Al2O3 may also be within the range between any two of the above mass percentages.
[0047] In some embodiments, the sum of the mass percentages of Li2O, Na2O and K2O is 4% to 10%. Alternatively, the sum of the mass percentages of Li2O, Na2O and K2O is 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%. Alternatively, the sum of the mass percentages of Li2O, Na2O and K2O may also be within the range between any two of the above mass percentages.
[0048] In some embodiments, the sum of the mass percentages of MgO, CaO, BaO and SrO is 14% to 23%. Alternatively, the sum of the mass percentages of MgO, CaO, BaO and SrO is 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5% or 23%. Alternatively, the sum of the mass percentages of MgO, CaO, BaO and SrO may also be within the range between any two of the above mass percentages.
[0049] In some embodiments, the melting temperature of the glass substrate for Micro LED is T2, 1400°C<T2<1500°C. Optionally, the melting temperature of the glass substrate for Micro LED is T2 is 1415°C~1495°C. Further optionally, the melting temperature of the glass substrate for Micro LED is T2 is 1415°C, 1420°C, 1425°C, 1430°C, 1435°C, 1440°C, 1445°C, 1450°C, 1455°C, 1460°C, 1465°C, 1470°C, 1475°C, 1480°C, 1485°C, 1490°C or 1495°C. Alternatively, the melting temperature of the glass substrate for Micro LED can also be within the range between any two of the above temperatures. It should be noted that the melting temperature of conventional TFT glass substrates is generally 1600°C~1700°C. The glass substrate for Micro LED of the present application has a lower melting temperature.
[0050] In some embodiments, the glass transition temperature of the glass substrate for Micro LED is T g , 660℃<T g<720℃. Optionally, the glass transition temperature of the glass substrate for Micro LED is 662℃~713℃. Further optionally, the glass transition temperature of the glass substrate for Micro LED is 662℃, 663℃, 665℃, 668℃, 670℃, 672℃, 675℃, 678℃, 680℃, 682℃, 685℃, 688℃, 690℃, 692℃, 695℃, 698℃, 700℃, 702℃, 705℃, 708℃, 710℃, 711℃, 712℃ or 713℃. Or the glass transition temperature of the glass substrate for Micro LED can also be within the range between any two of the above glass transition temperatures. It should be noted that the minimum glass transition temperature of traditional TFT glass substrates is above 700℃, and the glass substrate for Micro LED of the present application has a lower glass transition temperature.
[0051] In some embodiments, the clarifying temperature of the glass substrate for Micro LED is T3, 1200° C.<T3<1300° C. Optionally, the clarifying temperature of the glass substrate for Micro LED is 1219° C.~1268° C. Further optionally, the clarification temperature of the glass substrate for MicroLED is 1219°C, 1210°C, 1212°C, 1214°C, 1216°C, 1218°C, 1220°C, 1222°C, 1224°C, 1226°C, 1228°C, 1230°C, 1232°C, 1234°C, 1236°C, 1238°C, 1240°C, 1242°C, 1244°C, 1246°C, 1248°C, 1250°C, 1252°C, 1254°C, 1256°C, 1258°C, 1260°C, 1262°C, 1264°C, 1266°C or 1268°C. Alternatively, the clarification temperature of the glass substrate for MicroLED may also be within the range between any two of the above temperatures.
[0052] In some embodiments, the difference between the clarification temperature of the glass substrate for Micro LED and the upper limit of crystallization is ΔT, 100°C ≤ ΔT ≤ 176°C. Optionally, the difference between the clarification temperature of the glass substrate for Micro LED and the upper limit of crystallization is 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 173°C or 176°C. Alternatively, the difference between the clarification temperature of the glass substrate for Micro LED and the upper limit of crystallization may also be within the range between any two of the above differences.
[0053] In some embodiments, the upper limit of crystallization of the glass substrate for Micro LED is 1050°C to 1140°C. Optionally, the upper limit of crystallization of the glass substrate for Micro LED is 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C, 1130°C or 1140°C. Alternatively, the upper limit of crystallization of the glass substrate for Micro LED may also be within the range between any two of the above upper limits of crystallization.
[0054] In some embodiments, the elastic modulus of the glass substrate for Micro LED is E, 73Pa≤E≤91Pa. Optionally, the elastic modulus of the glass substrate for Micro LED is 73Pa, 74Pa, 75Pa, 76Pa, 77Pa, 78Pa, 79Pa, 80Pa, 81Pa, 82Pa, 83Pa, 84Pa, 85Pa, 86Pa, 87Pa, 88Pa, 89Pa, 90Pa or 91Pa. Alternatively, the elastic modulus of the glass substrate for Micro LED may also be within the range between the above two elastic moduli.
[0055] In some embodiments, the coefficient of thermal expansion of the glass substrate for Micro LED at 30°C to 350°C is CTE, and 53 / °C<CTE<66 / °C. Optionally, the coefficient of thermal expansion of the glass substrate for Micro LED at 30°C to 350°C is 53.1 / °C, 53.2 / °C, 53.3 / °C, 53.5 / °C, 53.8 / °C, 54 / °C, 54.2 / °C, 54.5 / °C, 54.8 / °C, 55 / °C, 55.2 / °C, 55.5 / °C, 55.8 / °C, 56 / °C, 56.2 / °C, 56.5 / °C, 56.8 / °C, 57 / °C, 57.2 / °C, 57.5 / °C, 57.8 / °C, 58 / °C, 58.2 / °C, 58.5 / °C, 58.7 / °C, 59 / °C, 59. .2 / ℃, 59.5 / ℃, 59.8 / ℃, 60 / ℃, 60.2 / ℃, 60.5 / ℃, 60.8 / ℃, 61 / ℃, 61.2 / ℃, 61.5 / ℃, 61.8 / ℃, 62 / ℃, 62.2 / ℃, 62.5 / ℃, 62.8 / ℃, 63 / ℃, 63.2 / ℃, 63.5 / ℃, 63.8 / ℃, 64 / ℃, 64.2 / ℃, 64.5 / ℃, 64.8 / ℃, 65 / ℃, 65.1 / ℃, 65.2 / ℃, 65.3 / ℃, 65.4 / ℃, 65.5 / ℃ or 65.56 / ℃. Alternatively, the thermal expansion coefficient of the glass substrate for Micro LED of 30℃~350℃ may be within the range between any two of the above thermal expansion coefficients.
[0056] In some embodiments, the sum of the mass percentages of Na2O and K2O is a, the sum of the mass percentages of Li2O, Na2O and K2O is b, the sum of the mass percentages of SiO2 and Al2O3 is c, and 0.14≤ :E≤0.5. The glass substrate prepared from the raw materials satisfying the above formula can make the glass have a more suitable surface resistivity. Optionally, : E is 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49 or 0.5. Or, :E can also be in the range between any two of the above values.
[0057] An embodiment of the present application provides a Micro LED, including any one of the above-mentioned glass substrates for Micro LED.
[0058] The following are specific embodiments
[0059] Example 1
[0060] Glass substrate for Micro LED:
[0061] Expressed as mass percentage on an oxide basis, it contains the following components:
[0062] 53% SiO2, 17% Al2O3, 1% Na2O, 2% K2O, 3% MgO, 14% CaO, 1% BaO, 0.7% SrO, 6% B2O3, 2% P2O5 and 0.3% ZrO2.
[0063] Preparation method of glass substrate for Micro LED:
[0064] (1) According to the above components, commonly used glass raw materials such as oxides and carbonates are selected, weighed to obtain raw materials with a total mass greater than or equal to 1000 g, and fully stirred and mixed to obtain a mixture.
[0065] (2) The mixture obtained in step (1) is placed in a platinum crucible greater than or equal to 400 ml, the platinum crucible is placed in a silicon-molybdenum furnace, the temperature is raised to 1600° C., and the mixture is melted and clarified for more than 8 hours, the mixture is homogenized and cast into a mold, and precision annealing is performed at an annealing temperature below 750° C. to obtain bulk glass.
[0066] (3) The block of glass is precisely wire cut, and both surfaces are ground and polished to obtain a glass sample with a diagonal length of 6 inches and a thickness of 0.7 mm.
[0067] The compositions of the glass substrate for Micro LED in Examples 2 to 30 are shown in Tables 1 to 5. The preparation methods of the glass substrate for Micro LED in Examples 2 to 30 are basically the same as those in Example 1, except that the compositions of the glass substrates in each example are different.
[0068] The performance of the glass substrates for Micro LED prepared in Examples 1 to 30 was tested.
[0069] Glass performance test:
[0070] (1) The high temperature viscosity test of the bulk glass prepared in each embodiment was carried out using a high temperature viscometer from ORTON, USA, to determine the clearing temperature T2 (10 2 dPa·s), melting temperature T3 (10 3 dPa·s).
[0071] (2) The thermal expansion performance of the glass samples obtained by precision wire cutting was tested using the PC402L horizontal dilatometer from NETZSCH, Germany, to determine the glass transition temperature T g (10 13.4 dPa·s), thermal expansion performance CTE (35℃~350℃).
[0072] The composition and properties of the glass in Examples 1 to 6 are shown in Table 1 below:
[0073] Table 1
[0074]
[0075] The composition and properties of the glass in Examples 7 to 12 are shown in Table 2 below:
[0076] Table 2
[0077]
[0078] The composition and properties of the glass in Examples 13 to 18 are shown in Table 3 below:
[0079] Table 3
[0080]
[0081] The composition and properties of the glass in Examples 19 to 24 are shown in Table 4 below:
[0082] Table 4
[0083]
[0084] The composition and properties of the glass in Examples 25 to 30 are shown in Table 5 below:
[0085] Table 5
[0086]
[0087] Referring to Tables 1 to 5 above, the glass transition temperatures T of each glass substrate in Examples 1 to 30 are g The temperature range of the heat treatment process is 662℃~713℃, the elastic modulus is 73Pa~91Pa, T3 (10 3 dPa·s) are all in the range of 1219℃~1268℃, T2 (10 2 dPa·s) are all within the range of 1415°C to 1495°C, which is less than 1500°C, and ΔT is within the range of 100°C to 176°C. The glass substrates in Examples 1 to 30 of the present application all have a relatively high glass transition temperature and a relatively low melting temperature.
[0088] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0089] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.
Claims
1. A glass substrate for Micro LED, characterized in that: The basic composition, expressed as mass percentage based on oxides, includes the following components: 53%~65% SiO2, 5%~17% Al2O3, 0~3% Li2O, 1%~10% Na2O, 0~2% K2O, 0.1%~10% MgO, 9%~16% CaO, 0~2% BaO, 0~3% SrO, 2%~6% B2O3, 0~3% P2O5 and 0.01%~1% ZrO2.
2. The glass substrate for Micro LED according to claim 1, characterized in that: The sum of the mass percentages of SiO2 and Al2O3 is 66%~75%.
3. The glass substrate for Micro LED according to claim 1, characterized in that: The sum of the mass percentages of Li2O, Na2O and K2O is 4%~10%.
4. The glass substrate for Micro LED according to claim 1, wherein: The sum of the mass percentages of MgO, CaO, BaO and SrO is 14%~23%.
5. The glass substrate for Micro LED according to claim 1, wherein: The glass substrate for Micro LED meets at least one of the following characteristics: (1) Melting temperature is T2, 1400℃<T2<1500℃; (2) Glass transition temperature is T g , 660℃<T g <720℃; (3) The clarification temperature is T3, 1200℃<T3<1300℃; (4) The difference between the clarification temperature and the upper limit of crystallization is ΔT, 100℃≤ΔT≤176℃.
6. The glass substrate for Micro LED according to claim 5, characterized in that: The sum of the mass percentages of Na2O and K2O is a, the sum of the mass percentages of Li2O, Na2O and K2O is b, the sum of the mass percentages of SiO2 and Al2O3 is c, 0.14≤ :E≤0.
5.
7. The glass substrate for Micro LED according to claim 1, wherein: The mass percentage of SiO2 is 56% to 63%; and / or the mass percentage of Al2O3 is 8% to 16%.
8. The glass substrate for Micro LED according to claim 1, wherein: The mass percentage of Li2O is 0% to 1%; and / or, the mass percentage of Na2O is 1% to 6%; and / or, the mass percentage of K2O is 0% to 1%.
9. The glass substrate for Micro LED according to claim 1, wherein: The mass percentage of MgO is 1% to 9%; and / or, the mass percentage of CaO is 10% to 16%; and the mass percentage of P2O5 is 0 to 2.5%.
10. A Micro LED, characterized in that: A glass substrate for Micro LED comprising the glass substrate according to any one of claims 1 to 9.
Citation Information
Patent Citations
Glass composition for substrate and method for producing the same
CN101835718A
Production method for glass plate and glass plate production device
CN102811959A
Glass for chemical strengthening and chemically strengthened glass
CN105813995A
Aluminosilicate glass, preparation method thereof, electronic display screen protection glass
CN109293234A
Aluminum borosilicate glass, preparation method thereof, composite glass and application thereof
CN118561515A